(untitled) (Revista de Investigaciones Universidad del Quindío, 2010)
We register the presence and distribution of an introduced population of chigüiros in the Quindío department, through field paths and geo referenciation of place of presence. Chigüiros are distributed from Maravélez valley until the sector of Piedras de Moler and in the low areas of the rivers Quindío, Barragán, Espejo and Roble, in jurisdiction of the municipalities of La Tebaida, Montenegro and Quimbaya. The composition of the groupsiss mall (non superior to three individuals), finding in major proportion more individuals solitary. We register the presence of juvenile individuals what indicate that the population is reproducing. We call the attention to the environmental authorities to evaluate the impact of the introduction of this mammal in the neotropical High And esecosystems.